Risk assessment behaviour when eating out in adults with food hypersensitivity - Rebecca C. Knibb; Lily Hawkins; Cassandra Screti; M. Hazel Gowland; Mamidipudi Thirumala Krishna; George du Toit; Christina J. Jones (Clinical and Translational Allergy, 2024)
Abstract Background Food hypersensitivity (FHS) management requires daily risk assessments of all food and drinks consumed to prevent unpleasant and potentially fatal adverse reactions. Most research has focussed on food allergy in children and families. Little is known about the impact on adults or those with other FHS, such as food intolerance or coeliac disease. This study assessed differences in practices and risk assessment behaviours when eating out for adults with FHS. Methods Adult UK residents (N = 930; 820 females, 90 males; 95% White; mean age 50 years [±16.6SD]), with food allergy (18%), food intolerance (23%) coeliac disease (44%) or multiple FHS (15%) completed an online survey. Results Adults checked information to identify foods causing a reaction always or most of the time when eating out. However, adults with food intolerance reported checking significantly less often than adults with other FHS (all ps < 0.001). Adults reporting more severe FHS, medical rather than self‐diagnosis of FHS, previous anaphylaxis, had called an ambulance or been in hospital due to a reaction checked information significantly more often (all ps < 0.001), but were also less confident in the information provided (all ps < 0.05). Adults with allergy, coeliac disease or multiple FHS were also less confident in written and verbal information provided than those with food intolerance (p < 0.01). The type of FHS, greater perceived severity of FHS and having a medical diagnosis consistently predicted risk assessment behaviours when eating out (all ps < 0.001). Conclusion Clinicians, patients and the food industry should be aware that the type of FHS, patient‐perceived severity and past experience of reactions affect risk assessment behaviours when eating out. This should be considered when providing clinical advice and emergency plans.